Play,dreams,and imitation in childhood - Piaget, Jean. (New York : Norton, 1962)
"Piaget's work is a cornerstone in development. His writing is long and laborious. He takes six pages to tell us that a 2 month old exhibits imitation behaviors. He was not an expert in parsimony. In his defense the translation from French is a bit awkward. What French I can read, of his work it is smoother than this translation. Case study gold, quoted as fact as if he had done something more significant than watch his own children and write down their behavior. No experimentally designed trials here. It's funny the same people and institutions who tout his great methods of research criticize Freud for his exact same research method: the case study. Many devout Piaget loyalists have never even read his original work. They've only been exposed to his work by text books in class. For this reason alone, I urge everyone to read as much source material as possible. Piaget is no exception. Get it, read it, make your own interpretation. Love it or hate it, you'll be wiser for the effort"--Amazon.com.
Includes index.
Keywords: Child psychology; Child development; Imitation; Play